Household Debt and Consumer Spending in Korea: Evidence from Household Data - Young Il Kim; Min Hwang (KDI Journal of Economic Policy, 2016)
Household debt in Korea raises concerns about the resilience of the economy due to its size and quality. Against this backdrop, we investigate if household leverage matters for private consumption in adverse economic environments even without severe financial disruptions. We find that the balance sheet positions in terms of the leverage ratio may weaken consumption growth. We also find that the depressive effect of debt on consumption may differ across types of consumer spending and household characteristics. In particular, the effects of indebtedness have been much stronger in relation to durable goods expenditures than in other areas. In addition, debtors in highincome (wealth) groups have also shown downward adjustments in consumption even more so than low-income (wealth) groups. These findings imply that debtors' precautionary behavior may serve as an important channel from leverage to consumer spending.
Keywords: D12; E21; E30; 330; Household debt; Consumption; Leverage